A microbial consortium from a biomixture swiftly degrades high concentrations of carbofuran in fluidized-bed reactors. Issue 10 (October 2016) - Castro-Gutiérrez, Víctor; Masís-Mora, Mario; Caminal, Glòria; Vicent, Teresa; Carazo-Rojas, Elizabeth; Mora-López, Marielos; Rodríguez-Rodríguez, Carlos E.
Graphical abstract: Highlights: Carbofuran-degrading microbial consortium obtained from a biopurification system. Removal of carbofuran up to 200 mg L −1 in batch bioreactors in less than 17 h. Removal of carbofuran (100 mg L −1 ) at a HRT of 23 h in continuous reactor operation. The consortium cross-degrades other carbamates: aldicard, methomyl and methiocarb. Consortium comprised relatives of Cupriavidus, Achromobacter and Pseudomonas genera. Abstract: An on-farm biopurification system (BPS) biomixture, with proven capacity to degrade carbofuran (CBF) was used as inoculum for a selective-enrichment process to obtain a bacterial consortium capable of using CBF as a sole source of carbon. Bacterial strains that comprise the consortium were identified as members of the genera Cupriavidus, Achromobacter and Pseudomonas . The consortium was tested in batch bioreactors, with initial CBF concentrations ranging from 50 to 200 mg L −1, in which complete degradation was attained in 16–17 h. Continuous operation of the bioreactor was optimized to achieve conditions of complete removal of up to 100 mg L −1 of CBF at a HRT of 23 h by the microbial consortium. Cross-degradation assays showed that the consortium was also capable of degrading high concentrations of other carbamates such as aldicarb, methiocarb and methomyl in batch bioreactors. The use of this consortium for the treatment of CBF and other carbamates at reactor scale represents a potential approach for the removal of these pesticides from agricultural wastewater, as an alternative to BPS.